Penanganan Covid-19 oleh Pemerintah Samoa Ditinjau dari Perspektif Human Security - Melpayanty Sinaga; Virgin Leony (Jurnal Multidisiplin Madani, 2022)
This paper aims to explain the handling of covid-19 by the government of Samoa from the perspective of human security. This study uses qualitative research methods and data collection through literature studies from books, journals, newspapers and news sources. The results of the study are that the handling of Samoa's handling of the Samoan virus is known as preparedness, policies in the land and sea transportation sector, following standard health protocols, learning from the experience of failing to handle the Spanish flu and measles outbreaks. The role of the Samoan government, the ministry of health as well as Miss Samoa community leaders have had a major impact in preventing the spread of COVID-19. This has resulted in the number of deaths due to COVID-19 in Samoa being not confirmed or the number infected with this virus being 0 (zero).